World Heritage - Harrison, Peter ([Australia] : The Department of the Arts, Sport, the Environment, Tourism and Territories, 1990)
Shows a close-up photograph of the surface of coral releasing many small pinkish eggs.
"Brain coral setting eggs, The Great Barrier Reef".
Catalogue record generated as part of a batch load.
Poster number 6 in a series of 9..
Keywords: Corals -- Queensland -- Great Barrier Reef -- Posters; Great Barrier Reef (Qld.) -- Posters